Factors Affecting the Union of Opening Wedge High Tibial Osteotomy Using a Titanium Wedge Plate - Nawas, Husam T. (Ochsner J, 2016)
BACKGROUND: Factors that can affect the success rate of high tibial osteotomy (HTO) include patient selection, surgical technique, type of fixation hardware, supplemental fixation, choice of bone graft, and rehabilitation protocol. The purpose of this study was to define the role of cortical hinge fractures in the risk of nonunion and collapse of opening wedge high tibial osteotomy. METHODS: A total of 60 patients (mean age, 40 years) who underwent 64 primary HTO procedures were identified from our operational database and observed at a mean follow-up of 2 years. Surgical correction was followed by immediate range of motion and a progressive weight-bearing protocol. Clinical and radiographic data were reviewed for patient demographics, bony union, cortical hinge fractures, loss of correction, and other complications. RESULTS: The average time to radiographic union was 14.8 weeks (range, 8-24). Loss of correction and/or collapse occurred in 6 cases (9.4%). Nine unrecognized cortical hinge fractures were retrospectively identified, of which 4 resulted in nonunion and collapse. We found a significantly higher incidence of unrecognized cortical hinge fractures in cases that collapsed (4/6, 66.7%) compared to cases that healed uneventfully (5/58, 8.6%) (P=0.003). CONCLUSION: A high index of suspicion must be maintained intraoperatively and postoperatively to identify and treat unstable constructs that increase the risk of nonunion and collapse after opening wedge HTO. This study's patient series explores the relationship between cortical hinge fracture and patient outcomes in the clinical setting by demonstrating a significantly higher rate of collapse and nonunion with unstable constructs.